Real time temperature measurement using gradient echo magnetic resonance imaging - Büyükgüngör, Volkan. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2008., 2008)
Heat induced local therapies play a signi cant role in several medical procedures, a major eld being tumor ablation. Regardless of the temperature range and the heat application method of these di erent hyperthermia applications, they all require the solution of the following problem: Determination of spatial and temporal distribution of temperature (thus the e ects and side e ects of treatment) within the applied region. A targeted temperature monitoring system with su cient capabilities would enable focusing, localization, thermal dose planning, collateral damage prevention and validation of treatment. First four of the above inherently need to be interactive, thus require real time monitoring. For a real-time application, underlying goal is to provide a relative or absolute temperature measurement, fast enough to use the temperature data to intervene with the medical procedure. MRTI (Magnetic Resonance Temperature Imaging) with PRF shift method is rst proposed as a way to provide fast temperature maps during thermal therapies by Ishihara in 1992. It provides a way to use the phase images from GRE sequences to extract temperature di erence information between successive acquisitions. In this thesis, an attempt is made to implement all parts of an MR-based temperature measurement system, which consists of an appropriate GRE sequence, post processing, and visualization code. The system will have the potential of being adapted to an MRI console in order to create an interactive real-time temperature monitoring application.|Keywords: Invivo Temperature Mapping, Magnetic Resonance Imaging, MRTI (MR Temperature Imaging)
Keywords: Magnetic resonance imaging.; Temperature measurements.